Thermochemical pre- and biological co-treatments to improve hydrolysis and methane production from poultry litter - Costa, J. C. (2012)
The biochemical methane potential (BMP) of raw poultry litter waste was assessed in batch assays. Biological co-treatment with Clostridium cellulolyticum, Caldicellulosiruptor saccharolyticum and Clostridium thermocellum as bioaugmentation strains, and thermochemical pre-treatments with lime and sodium hydroxide performed at different temperatures and pressures were applied as strategies to improve the BMP by favouring the hydrolysis of the cellulolytic material in the waste. Anaerobic digestion of the raw waste allowed a specific methane production of 145 ± 14 L CH4 kg−1 VS, with 1% total solids and 0.72 g VSinoculum g−1 VSwaste. The pre- and co-treatments contributed to a significant increase (up to 74%) in the waste solubilisation when using C. saccharolyticum, but methane production did not improve considerably. Therefore, the conversion of soluble organic matter to methane was the limiting step of the anaerobic digestion process of poultry litter waste.